1 Maccabees - Bartlett, John R. (John Raymond) (Guides to Apocrypha and Pseudepigrapha., 1998)
This is a book for anyone interested in the political and cultural results of the entry of the small state of Judah and its capital Jerusalem into the wider Hellenistic world in the second century BCE. In particular it forms a helpful introduction to the biblical writing called 1 Maccabees, which is preserved in the Apocrypha. 1 Maccabees is a history of the rebellion of the Jews against their Syrian rulers in the 160s BCE. The rebellion's leader was Judas Maccabee, and from his family and its success sprang a dynasty that ruled Judah for the century before the arrival of Herod the Great. The.